Neurath on Verstehen. (15th July 2019) - Uebel, Thomas
Abstract: This paper argues for a broadened understanding of the social scientific thought of a leading logical empiricist and advocate of the unity of science. Often portrayed as a reductive physicalist on account of his temperamental interventions against geisteswissenschaftliche obscurantists in the time of the Weimar Republic, Otto Neurath in fact was a defender and practitioner of interpretive methods who warned against their abuse inside and outside of academic social science and history. After placing Neurath's efforts in the context of the Vienna Circle, his talk of "social behaviorism" and his criticisms of Max Weber are clarified (both represent prominent stumbling blocks for an appreciation of Neurath's views) and his view on the role of empathetic understanding is reconstructed. Further support for this interpretation is then adduced from various instance of his pre‐Vienna Circle work (incl. his critique of Spengler and his own work in economic history and history of ideas). Having been trained in the Historical School, Neurath never abandoned his hermeneutic insights but sought to integrate them in a non‐dichotomous conception of science.